Ozonation as cyanophyta control method for water treatment - Suwanvitaya, Patcharaporn; Singhaphen, Sudarat (Engineering and Applied Science Research, 2018)
A problem with the use of chemical oxidants for algae control in water treatment processes is an incomplete destruction of algal cells, leading to the clogging of the filter media. Ozone, with its high oxidizing power, can be used not only for treating many types of organic contaminants but also for destroying microorganisms. This study investigated the effect of ozone in controlling an algal population. The sample for the study, obtained from a raw water reservoir of the MWA Bangkhen Water Treatment plant (Thailand), was cultured in Bold’s Basal medium and used as a study population. Morphological identification of algae in raw water sample and cultured sample (study population) revealed that the predominant organisms were Chlorophyta, Cyanophyta and Bacillariophyta. Identification by PCR-DGGE and DNA sequencing of Cyanophyta in raw water and in the study population showed that the predominant algae were Oscillatoria sp. (99% similarity), Limnothrix sp. (99% similarity) and Merismopedia sp. (93% similarity). Ozonation was conducted using ozone gas from a corona discharge type generator, generated at the rate of 3.7 mg/min. The results showed that ozone successfully destroyed algae. With 15.4 mg O3/L, the initial population of 1,021 μg chlorophyll-a/L was reduced by 72.4%. This was equivalent to the removal rate of 47μg chlorophyll-a/mg O3. The re-culturing of the ozonated algae population, both in supernatant and sludge, yielded no change in chlorophyll-a content. Also no presence of a cyanophyta DNA fingerprint was observed on agarose gel. This indicated that regrowth did not occur and ozonation completely destroyed all the algae.